2019
DOI: 10.1177/1350650119842683
|View full text |Cite
|
Sign up to set email alerts
|

Variation of zero entraining velocity dimple in grease-lubricated reciprocating motion

Abstract: In this study, experiments were conducted on a ball-on-disk test rig using optical interferometry to explore the variation in grease film thickness under zero entraining velocity reciprocating motion. The steel ball and the sapphire disk move at equal speeds but in opposite directions within a triangle wave. Three types of commercially available bearing greases with different consistencies, Centoplex 2EP, Centoplex 3, and MP-3, were used in these experiments. The variations in the surface dimple phenomenon wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Starvation is necessary to happen for a longer term, and the more viscous of the base oil and the higher the NLGI grade, the longer time the lubrication is maintained. Wang et al 26 supported the observation that the existence time of the bled oil for C3 grease is shorter than that of MP-3 grease.…”
Section: Steady-state Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Starvation is necessary to happen for a longer term, and the more viscous of the base oil and the higher the NLGI grade, the longer time the lubrication is maintained. Wang et al 26 supported the observation that the existence time of the bled oil for C3 grease is shorter than that of MP-3 grease.…”
Section: Steady-state Resultsmentioning
confidence: 82%
“…As has been pointed out by Wang et al, 26 the National Lubricating Grease Institute (NLGI) grade and the viscosity of the base oil affects not only the bled oil film formation in ZEV reciprocating motion but also the lubrication performance. Starvation is necessary to happen for a longer term, and the more viscous of the base oil and the higher the NLGI grade, the longer time the lubrication is maintained.…”
Section: Steady-state Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Wong et al (2018) offered an idea of making the bearing surfaces different in affinity to oil to facilitate hydrodynamic lubrication for ZEV contacts. Wang et al (2019) experimentally explored the variation in grease film thickness under ZEV reciprocating motion. Their results showed that the grease consistency exerted a significant influence on the surface dimple and the starvation severity.…”
Section: Introductionmentioning
confidence: 99%